EFEKTIVITAS PENGGUNAAN MODEL MULTIREPRESENTASI DALAM PEMBELAJARAN FLUIDA DINAMIS TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 LANGOWAN - Korengkeng, Claudia Brigita; Marianus, Marianus; Mongan, Satyano Wim (LPPM Politeknik Saint Paul Sorong, 2024)
The study aims to determine the effectiveness of the use of multirepresentation models in learning dynamic fluids on the learning result of students in class XI SMA Negeri 1 Langowan. With this type of research, namely quantitative research, true-experimental method with pretest-posttest control group design research design, the sample studied in the experimental class and control class amounted to 25 people determined based on random sampling technique. The population taken in this study were all grade XI students at SMA Negeri 1 Langowan. The research data was generated using a 12-item test instrument in the form of multiple choice questions. Based on the results of data processing, it was found that the average posttest value in the experimental class was 67.68 compared to the average posttest of the control class of 40.32. Then a statistical analysis was carried out in the form of T test analysis (Independent sample t-test) which showed a difference between student learning outcomes in experimental and control classes. Thus, the use of multirepresentation model is effective in improving the learning result of grade XI students at SMA N 1 Langowan. Thus it can be concluded that there is an increase in student learning result in the use of multirepresentation models in dynamic fluid learning